A LATE MIOCENE MAMMAL ASSEMBLAGE REVEALS A COMPLEX TAPHONOMIC HISTORY IN FLUVIAL DEPOSITS OF CENTRAL ARGENTINA. (4th May 2023) - Montalvo, Claudia I.; Tomassini, Rodrigo L.; Cerdeño, Esperanza; Fernández, Fernando J.
ABSTRACT: Micro- and macromammal remains from Cerro La Bota (late Miocene; La Pampa Province, Argentina) are taphonomically analysed. All remains form a single sample recovered from Chasicoan sediments (facies FA2) of the Cerro Azul Formation, constituted by a lateral and vertical erosive superposition of sandstone and conglomeratic bodies, formed by episodic development of perennial streams without flow division on a loessic substrate. The analysis reveals that micro- and macromammal remains originally accumulated independently and differently. Once each type of accumulation was buried in a loessic context, the development of streams gave place to a reworking process of fossils that were finally incorporated together into the stream channel. Taphonomic characteristics of micromammals are interpreted as the result of the leftover prey accumulated by predators, probably at a den site. Instead, the macromammals respond to an attritional accumulation of individuals inhabiting the area. Even considering the reworking as an important process that affected this assemblage, the taxonomic and taphonomic evidences suggest a relatively short time for its formation. The different taphonomic histories of the remains evidence a complex association that differs from other assemblages from the Cerro Azul Formation previously analysed, and it is here assigned to the channel-lag taphonomic mode.